Diazine-based thermally activated delayed fluorescence chromophores. (April 2022) - Achelle, Sylvain; Hodée, Maxime; Massue, Julien; Fihey, Arnaud; Katan, Claudine
Abstract: Diazines are electron deficient six-membered aromatic rings heterocycles which have successfully been employed in the design of a wide range of push-pull chromophores for various applications in the field of organic electronics and optoelectronics. For instance, some have been specifically designed to be inserted in the electroluminescent emission layer of organic light emitting diodes (OLED). OLED technology has continuously evolved and is currently used in industry for display and lighting purposes, offering many advantages including low turn-on voltage and power consumption. In the prospect to further reduce energy waste, a third generation of OLED based on thermally activated delayed fluorescence (TADF), which allows harvesting both triplet and singlet excitons, attracts increasing attention from the scientific community. In this review, we provide a comprehensive overview of the present status of diazine-based dyes developed for TADF. The pyrimidine core is by far the most used and has demonstrated deep blue, blue or sky-blue and green emission when combined with carbazole, acridan and phenoxazine fragments, respectively. Further design of TADF emitters is desirable to afford red OLED and both the pyrazine and pyridazine cores have been scarcely explored. Graphical abstract: Image 1 Highlights: Pyrimidine has been extensively used in the structure of TADF chromophores. Bulky of spiro electron-donating parts required substituents of diazine TADF chomophores. Structure-properties relationships were established through the scope of TADF and OLED performances.